Salivary IgA as a Predictor of Upper Respiratory Tract Infections and Relationship to Training Load in Elite Rugby Union Players. Issue 3 (March 2020) - Tiernan, Caoimhe; Lyons, Mark; Comyns, Tom; Nevill, Alan M.; Warrington, Giles
Abstract : Abstract: Tiernan, C, Lyons, M, Comyns, T, Nevill, AM, and Warrington, G. Salivary IgA as a predictor of upper respiratory tract infections and relationship to training load in elite rugby union players. J Strength Cond Res 34(3): 782–790, 2020—Upper Respiratory Tract Infections (URTI) are among the most common illnesses reported in athletes. An URTI can result in missed training days, which in turn may lead to performance decrements. The purpose of this study was to investigate the use of salivary immunoglobulin A (sIgA) as a predictor of URTI, while also exploring the relationship to weekly training load in elite rugby union players. Nineteen male elite rugby union players provided morning saliva swabs, biweekly (Monday and Friday), over a 10-week training period. Participants completed an illness log documenting symptoms of URTI. Session Rate of Perceived Exertion (sRPE) was collected to determine training load (sRPE × session duration). Weekly training load was also calculated. Logistic regression was used to analyze the relationship between incidences of URTI with sIgA and training load. Multilevel regression was conducted to compare associations between sIgA and training load. The results found that the likelihood of suffering from an URTI increased when sIgA significantly decreased ( p = 0.046). Where sIgA decreased by 65% or more, a player was at a greater risk of contracting an URTI within the following 2 weeks. No association was found between sIgA and training load. In conclusion, sIgA may be a useful predictor for determining the likelihood of players contracting an URTI. This will allow the coach to make informed decisions on training status, helping reduce the risk of players missing training, which may have performance decrements. Coaches will benefit from the fast, easy, and instant results available, to analyze a player's immune function.